1986
DOI: 10.1097/00003446-198612000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Four Dichotic Speech Tests Before and After Temporal Lobectomy

Abstract: Thirty patients were tested with four dichotic speech tests before and after temporal lobectomy for control of intractable seizures. Ipsilateral ear scores improved on all tests postoperatively; these improved scores reached statistical significance for the Staggered Spondaic Word Test and for consonant-vowel syllables. This result, combined with a nonsignificant decrease for contralateral ear scores, produced postoperative increase in the ipsilateral minus contralateral ear difference scores, similar to previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Hippocampal sclerosis may influence organized processing of bilateral ACs, in accord with recent conceptualizations of epilepsy as a network disease [54]. To date, various cognitive and psychiatric impairments [55] and CAP impairments have been found in patients with mTLE [2,5,6,[8][9][10][11][12][13]. Auditory dysfunction may be caused by impaired connectivity resulting from seizure propagation between the hemispheres.…”
Section: Significance Of Plvs In Mtlementioning
confidence: 61%
See 1 more Smart Citation
“…Hippocampal sclerosis may influence organized processing of bilateral ACs, in accord with recent conceptualizations of epilepsy as a network disease [54]. To date, various cognitive and psychiatric impairments [55] and CAP impairments have been found in patients with mTLE [2,5,6,[8][9][10][11][12][13]. Auditory dysfunction may be caused by impaired connectivity resulting from seizure propagation between the hemispheres.…”
Section: Significance Of Plvs In Mtlementioning
confidence: 61%
“…In this context, altered CAP refers to changes in the perceptual processing of auditory information in the central nervous system despite normal hearing sensitivity, exhibited as poor auditory discrimination performance, auditory pattern recognition and temporal differentiation [2][3][4]. For example, patients with mTLE show decreased performance in dichotic listening [5][6][7] to both verbal and nonverbal sounds [8], poor performance in anisochrony or irregularity discrimination of rapid auditory sequences [9], and decreased temporal processing in the Gaps-In-Noise test [10] and the duration pattern sequence test [11]. Intractable patients with right mTLE are at risk of speech recognition impairment in real-world listening environments compared with extratemporal lobe epilepsy [12].…”
Section: Introductionmentioning
confidence: 99%
“…Collard et al 32 , using verbal dichotic tests in epileptic patients, observed after temporal lobectomy an improvement of the responses in the ipsilateral ear and suggest that paroxysmal activity produces an inhibitory influence in contralateral cortex function.…”
mentioning
confidence: 98%
“…Working in animals, Masterton (2) conclusively demonstrated that the temporal pole and the amygdala are involved in auditory processing, and it is also known that the geniculoamygdaloid pathway plays an importantfunctional role in hearing [1][2][3]. Beginning in 1961, Kimura (4) showed that anterior temporal lobectomy in humans resulted in partial or total abolition of dichotic listening test scores for sounds or messages delivered to the ear contralateral to the operated temporal lobe [4][5][6]. In 1972, Berlin (7) detected subjective auditory deficits following anterior temporal lobectomy [7][8][9] bat only the investigation of Jacobson (10) included objective electrophysiological data.…”
mentioning
confidence: 99%